Hambatan Komunikasi Guru dan Siswa serta Implikasinya terhadap Efektivitas Pembelajaran - Ester Piani Telaumbanua; Ayu Mora Simarmata; Angel Kristina; Joyce Inori Siregar; Mutiara Seven Manalu; Apiza Aulia; Debora Novita Simbolon; Arwan Kusma Waruwu; Hegel Chris Haganta Barus; Chintya Aprella Nainggolan; Fauzi Kurniawan; Anifah (STKIP Subang, 2026)
This study examines communication barriers between teachers and students in the learning process at UPT SD Negeri 066054 Medan Denai. Effective communication is essential for delivering learning materials clearly and fostering student engagement. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation involving one teacher and 20 students. The findings reveal that teachers employ both verbal and non-verbal communication, yet challenges remain in maintaining student attention and creating an open communication climate. Interpersonal communication significantly influences learning effectiveness, but barriers such as unclear messages, authoritarian styles, and psychological constraints reduce student participation. This study highlights the importance of empathetic communication strategies, adaptive teaching methods, and the integration of media to overcome communication barriers and enhance learning outcomes. The implications suggest that schools and policymakers should provide training programs to strengthen teachers’ communication skills and promote inclusive classroom environments.